Meet the New Es: Empathy, Engagement, Equity, and Ethics in Public Administration. (3rd September 2022) - Meyer, Seth J.; Johnson, Richard Greggory; McCandless, Sean
Abstract: With growing discussion and action around inequality, climate change, and a global pandemic, do the current pillars of public administration, economy, efficiency, and effectiveness, also known as the 3Es, meet the needs of the public administration? We propose that there are new pillars which better respond to 21st century problems in ways not addressed through values of efficiency, effectiveness, and economy. In this article, we will explore these new 4Es (empathy, engagement, equity, and ethics) in more depth, as well as articles in the first half of this double special issues on the topic. Through this article and special issue, we are eager to move the field of public administration forward towards creating more engaged, empathetic, equitable, and ethical public and nonprofit organizations.